Tindak Tutur dalam Proses Ujian Skripsi Mahasiswa STAIN Sultan Qaimuddin Kendari - Bat Mang (Tarbawiyah Jurnal Ilmiah Pendidikan, 2016)
The purpose of this research is in order to describe and to explain the usage of form of speech act, pattern of speech act, the function of speech act, the application of conversation cooperation principal, abd the abuse of conversation cooperation principal in STAIN Qaimuddin Kendari. This research use qualitative approach by content analysis student and mini thesis examination process. Data collecting technical be done by recording the conversation of mini thesis examination and to transcript in conversation transcription form. The research result point out whereas there is differentiation in usage of form of speech act, pattern of speech act, function of speech act, the application of cooperation principal and the abuse of cooperation principal in mimi thesis examination process between tester lecturer ask and give the description to university student with the university student when answer and description the opinion to tester lecturer.